Development of distributed institutional leadership capacity in online learning and teaching project : final project report. - Chesterton, Paul; Duignan, Patrick; Felton, Emma; Flowers, Karen; Gibbons, Pam; Horne, Marj; Thomas, Theda (Carrick Institute for Learning and Teaching in Higher Education, 2008)
Final report of a project that was designed to develop distributed institutional leadership capacity in the pedagogical and evaluative dimensions of online learning and teaching in the host university. The approach taken in the project was to develop leadership capacity among six academic staff (online advisers) for application at a university-wide level, but also in relation to the specific needs and circumstances of the various campus, faculty and discipline contexts. The online advisers were engaged in specialised training in pedagogical and evaluative dimensions of online learning and teaching and in leadership, and then undertook a range of activities at campus, faculty and university levels through which they applied their developing leadership capacities. The project defined leadership as providing direction, and exercising influence. The multi-campus setting highlighted the importance of communication and relationships in the development of leadership capacity. The transferability of the approach adopted in the project to other institutions will depend on the extent to which it can be tailored to address specific needs and contexts, and the extent to which a supportive framework such as that experienced at ACU National is available.